2010
DOI: 10.5194/acp-10-5107-2010
|View full text |Cite
|
Sign up to set email alerts
|

Size distributions of elemental carbon and its contribution to light extinction in urban and rural locations in the pearl river delta region, China

Abstract: Abstract. Elemental carbon (EC) in size-segregated aerosol samples were determined at five urban, one suburban, and one rural locations in the Pearl River Delta region in South China during 2006-2008 period. The size modal characteristics of EC were different at the urban and suburban/rural locations. The urban EC had a dominant condensation mode with a mass median aerodynamic diameter (MMAD) in the 0.36-0.43 µm range and a slightly less abundant mode in the droplet mode size (MMAD: 0.8-1.1 µm), while the subu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 52 publications
(55 reference statements)
7
63
2
Order By: Relevance
“…Previous studies demonstrated an important role of EC in atmospheric light extinction in the PRD region (e.g., Yu et al, 2010). However, the aerosol measurements of EC in China reported so far have been primarily based on bulk techniques (Wu et al, 2012) that could not provide sufficient information on compositions of EC-containing particles, including the coating materials at single particle level.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies demonstrated an important role of EC in atmospheric light extinction in the PRD region (e.g., Yu et al, 2010). However, the aerosol measurements of EC in China reported so far have been primarily based on bulk techniques (Wu et al, 2012) that could not provide sufficient information on compositions of EC-containing particles, including the coating materials at single particle level.…”
Section: Introductionmentioning
confidence: 89%
“…Study in this region also revealed that urban EC had a dominant condensation mode and a less abundant droplet mode, while the suburban/rural EC had a prominent mode in the droplet mode, due to the growth of smaller particles when the air mass moved from the urban source regions to the suburban/rural site (Yu et al, 2010). In Paris, Healy et al (2012) showed that EC in the droplet mode, Fig.…”
Section: General Characteristics Of Ec-containing Particlesmentioning
confidence: 99%
“…Considering that the LII technique is specific to BC mass determination which is independent of BC mixing state, the size distribution reported using LII is able to represent the size distribution of the BC core. A study using a micro-orifice uniform deposit impactor (MOUDI) found a EC mass size distribution in the PRD exhibiting three modes peaking at ∼ 300, ∼ 900 and ∼ 5000 nm (Yu et al, 2010), implying a substantial coating of BC particles, and a diameter amplification of 3. BC sizing from LII is based on volume-equivalent diameter (VED), while MOUDI is based on aerodynamic diameter.…”
Section: Mie-modeled Light Absorption Enhancement Factor (E Abs )mentioning
confidence: 99%
“…S9). A detailed discussion on the comparison of these two measurements can be found in the Supplement (Yu et al, 2010;Huang et al, 2011Huang et al, , 2012. The size-resolved scavenged/activated fractions (Nf scav ) of the BC-containing particles and all the detected particles were further investigated as a function of their size (Fig.…”
Section: Fractions Of Bc Incorporated Into Cloud Droplets 321 Size-mentioning
confidence: 99%